Normalized Double-Talk Detection Based on Microphone and AEC Error Cross-Correlation - Iqbal, Mohammad Asif; Stokes, Jay; Grant, Steven L. (Institute of Electrical and Electronics Engineers, Inc., 2007)
In this paper, we present two different double-talk detection schemes for Acoustic Echo Cancellation (AEC). First, we present a novel normalized detection statistic based on the cross-correlation coefficient between the microphone signal and the cancellation error. The decision statistic is designed in such a way that it meets the needs of an optimal double-talk detector. We also show that the proposed detection statistic converges to the recently proposed normalized cross-correlation based double-talk detector Bennesty2000, the best known cross-correlation based detector. Next, we present a new hybrid double-talk detection scheme based on a cross-correlation coefficient and two signal detectors. The hybrid algorithm not only detects double-talk but also detects and tracks any echo-path variations efficiently. We compare our results with other cross-correlation based double-talk detectors to show their effectiveness.